Foreign Direct Investment and the Evolution of the Position of Poland's Economy in the Global Economy and the Economy of the European Union - Gorynia , Marian; Trąpczyński , Piotr (Studia Oeconomica Posnaniensia, 2026)
This article analyses the changing position of the Polish economy in relation to the world economy and the European Union economy. The first aim of the paper is to identify regularities that occurred in the processes investigated during the period under study. The conducted analysis, which covers the years 2003-2012, concerns changes in gross domestic product, changes in inward foreign direct investment and changes in outward foreign direct investment. The second aim of the paper is to forecast how different variables related to the internationalisation of the Polish economy will develop in the future and to formulate some recommendations with regard to economic and corporate policy.